Alternative Splicing: A New Cause and Potential Therapeutic Target in Autoimmune Disease - Ren, Pingping; Lu, Luying; Cai, Shasha; Chen, Jianghua; Lin, Weiqiang; Han, Fei (Frontiers in Immunology, 2021)
Alternative splicing (AS) is a complex coordinated transcriptional regulatory mechanism. It affects nearly 95% of all protein-coding genes and occurs in nearly all human organs. Aberrant alternative splicing can lead to various neurological diseases and cancers and is responsible for aging, infection, inflammation, immune and metabolic disorders, and so on. Though aberrant alternative splicing events and their regulatory mechanisms are widely recognized, the association between autoimmune disease and alternative splicing has not been extensively examined. Autoimmune diseases are characterized by the loss of tolerance of the immune system towards self-antigens and organ-specific or systemic inflammation and subsequent tissue damage. In the present review, we summarized the most recent reports on splicing events that occur in the immunopathogenesis of systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) and attempted to clarify the role that splicing events play in regulating autoimmune disease progression. We also identified the changes that occur in splicing factor expression. The foregoing information might improve our understanding of autoimmune diseases and help develop new diagnostic and therapeutic tools for them.